THE EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON STOCK PRICES IN PROPERTY & REAL ESTATE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020-2022 - Divya, Trisah; Br Sipayung, Risa Fransiska; Cahyani, Mutiara (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
This study was conducted to test the impact of each variable that has been determined simultaneously or partially. Through a population of 87 companies and based on the conditions that the author has determined, a sample of 57 companies was obtained. This quantitative study uses secondary data sources that are measured from a ratio scale for statistical management. This study uses multiple linear regression analysis. The analysis obtained from the F test showed that CR & DER had a significant positive impact on stock prices. Then, from the t-test (partial), CR with partial has a significant negative effect on stock prices, but DER does not have a significant effect on stock prices.